COACHING FOR PHYSICAL CONDITION IMPROVEMENT OF SIDOARJO FOOTBALL CLUB PLAYERS BASED ON SPORT SCIENCE - Puriana, Ramadhany Hananto; Wahyono, Muhammad; Kusuma, Angga Indra; Utamayasa, I Gede Dharma; Mardhika, Riga (Antis-publisher, 2026)
Objective: This community service program aimed to improve the physical condition of football players at a football club in Sidoarjo Regency through sport science–based assistance. Method: The program involved needs analysis, initial physical fitness assessment, assistance in designing and applying physical conditioning programs, and evaluation of outcomes. Educational sessions and practical on-field mentoring were provided to the coaches and players. Results: The program resulted in enhanced understanding of sport science-based physical training, leading to improvements in several components of players’ physical conditions. Coaches and players gained valuable knowledge about the importance of structured physical training. Novelty: This initiative bridged the gap between theoretical sport science principles and their practical application in a local football club, offering a systematic, sustainable physical training guideline. It exemplifies the role of physical education lecturers in developing sports performance at the local level.